Historical Metal works named Warsaw in Iran - KARAMIAN, Gholamreza (Historia i Świat, 2020)
Since long times ago, the artists of Lorestan, have been earning their livelihood through making various types of handicraft a valuable art piece deeply rooted in the province’s history called nickel silver crafts. In Farsi, varsho is actually the word ‘War-saw’. What is the reason for such labeling of these works of art in the Qajar and Pahlavi periods in Iran? Lorestan artists in Borujerd town created such magnificent art at that time. We still don’t know the reason for this naming, but one thing is clear, such metalwork is part of the history of art in both Poland and Iran.